Majority-Muslim hate crimes in England: an interpretive quantitative analysis - Friedrichs, J (Taylor and Francis, 2021)
This article draws on police data about racial and religious hate crimes, deriving insights on majorityminority relations from the identities of complainants and suspects as recorded in the database. Given intense public interest in Islamophobia, the focus is on majority-Muslim hate crimes with view to understanding patterns of perpetration and victimization in the context of community relations. To make the most of a patchy evidence base, I combine descriptive inference with contextual understanding gleaned from discussions with hate crime practitioners in police, local government and civil society. Examining the North English districts of Bradford and Calderdale, I find that hate crime practitioners privilege data quantity over quality; attribute the increase of recordings in recent years to better reporting; and explain the higher incidence of hate crimes late at night and during weekends with alcohol and nightlife socializing. I also find that minorities, whether Asian Muslim or White British, are overrepresented as victims in their residential area; find no correlation between dramatic events and the incidence of hate crimes; and find more victimization among male than female Muslims, questioning the narrative of “gendered Islamophobia.”